GEOCHEMISTRY OF SEABED AND COASTAL SEDIMENTS IN LIMAU WATERS AREA - Zulfikar, Muhammad; Saputro, Eko; Albab, Ali; Rahardiawan, Riza (Marine Geological Institute of Indonesia, 2025)
Sediment provenance and weathering history are used to understand sedimentary processes and to explore mineral potential in coastal–marine systems in the Limau Waters. Therefore, the characteristics of seabed and coastal sediments need to be determined. This study aims to identify the source rocks, paleoweathering signatures, and sediment maturity of both seabed and coastal sediments through a geochemical approach. A geochemical approach that integrates major oxide and rare earth element (REE) analyses, the paleoweathering, and sediment maturity indices, is used to identify the source rocks of these sediments. Major oxides elements were measured using X-ray fluorescence (XRF) and REE concentrations were determined using inductively coupled plasma - optical emission spectrometry (ICP-OES) and inductively coupled plasma optical - mass spectrometry (ICP-MS). Geochemical discrimination diagrams indicate that seabed sediments are mainly derived from intermediate to felsic igneous rocks with higher compositional maturity, whereas coastal sediments are influenced by mafic volcanic rocks and are comparatively immature in composition. Both sediment types exhibit weak chemical weathering (CIA < 70), suggesting limited alteration of young volcanic sources. The CIA–ICV relationships portray contrast sediment transport and depositional processes between the coastal and marine environments. This study is expected to provide a geochemical-based framework for provenance analysis and to support the development of insights for future marine mineral exploration in the Limau Waters area.